PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS PQ4R (PREVIEW,QUESTION, READ, REFLECT, RECITE, DAN REVIEW) PADA MATERI PERJUANGAN KERAJAAN BANTEN MELAWAN PENJAJAHAN BELANDA - Veronika Susanawati; Elis Setiawati (Swarnadwipa, 2020)
The Purpose of developing research module of PQ4R’s based is to produce modul. Products that are tested by experts or experts both physically and by design. This research method module is research and development research which is carried out referring to Erni's research using the level 1 development model that is up to tested products Level 1 product development includes identification of potentials and problems in literature review and relevant research, product design, product validation and tested design. The results of this study show that product validation, namely the pq4r-based module is carried out twice in the first stage, validation is carried out on the design aspects and the module material aspects in the design aspects. obtained a module feasibility level of 62.5% with a feasible category Then in the material aspect, the feasibility percentage was obtained at 6 10 9.2% after the product was revised according to the suggestion, then re-validated in the second validation, the percentage of eligibility in the design aspect was obtained. ar 87% and on the material aspect 84% with very eligibility criteria, thus it can be concluded that the product or model developed has been tested byexperts with criteria very suitable for use in learning.